Micro Finance for the Protection Of Women’s rights in India - Hira Najam; Bulbul Dhar James (International Journal of Small and Medium Enterprises and Business Sustainability, 2021)
India, which largely represented Women, SCs/STs/OBCs and other weaker sections of the society basically had no livelihood security in its rural areas. Microfinance plays a very important and catalytic role in activating the factors of production leading to the overall economic and social development by facilitating the enjoyment of right to work, right to social security, right to development and right to adequate standard of living in India. Microfinance has been a boon to potential rural entrepreneurs. It promotes mutual help and co-operation among members. The institutions which provide microfinance services include NABARD, SIDBI, and NBFCs etc. The present piece of study puts a light on not only the real effectiveness and impact of microfinance by converting the poor into producers but also ensures microfinance programs compliances with right-based norms and principles.